2012
DOI: 10.1183/09031936.00193411
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity knee extensor training restores skeletal muscle function in COPD patients

Abstract: Improving reduced skeletal muscle function is important for optimising exercise tolerance and quality of life in chronic obstructive pulmonary disease (COPD) patients. By applying high-intensity training to a small muscle group, we hypothesised a normalisation of muscle function.Seven patients with COPD performed 6 weeks (3 days?week -1 ) of high-intensity interval aerobic knee extensor exercise training. Five age-matched healthy individuals served as a reference group. Muscle oxygen uptake and mitochondrial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 37 publications
6
56
1
1
Order By: Relevance
“…Against the hypothesis of a disease-specific myopathy are the following: (1) many functional and cellular findings in COPD are identical to those of disuse; (2) limb muscle is trainable, because training has been shown to improve muscle strength and endurance, oxidative enzyme activities, fiber cross-sectional area, and muscle capillarization, at least in some patients (307,310); (3) in a small study, highintensity aerobic interval training was shown to restore work performance and oxidative capacity of the quadriceps to a level similar to that found in sedentary individuals (312); and (4) the fact that full recovery of muscle function is unusual does not necessarily indicate a myopathy, because the duration of the training program may be too short to normalize alterations that have developed over several decades (313,314), or early ventilatory limitation may compromise the ability to tolerate sufficient muscle stimulus to improve global or cellular function (311).…”
Section: Disuse Versus Myopathymentioning
confidence: 90%
“…Against the hypothesis of a disease-specific myopathy are the following: (1) many functional and cellular findings in COPD are identical to those of disuse; (2) limb muscle is trainable, because training has been shown to improve muscle strength and endurance, oxidative enzyme activities, fiber cross-sectional area, and muscle capillarization, at least in some patients (307,310); (3) in a small study, highintensity aerobic interval training was shown to restore work performance and oxidative capacity of the quadriceps to a level similar to that found in sedentary individuals (312); and (4) the fact that full recovery of muscle function is unusual does not necessarily indicate a myopathy, because the duration of the training program may be too short to normalize alterations that have developed over several decades (313,314), or early ventilatory limitation may compromise the ability to tolerate sufficient muscle stimulus to improve global or cellular function (311).…”
Section: Disuse Versus Myopathymentioning
confidence: 90%
“…The exercises within the RT regimen target muscles with decreased strength/endurance (compared to healthy individuals), muscles which are important for upper extremity activities of daily living, and muscles which are important for walking [15][16][17][18]. All exercises were executed using a single limb at a time, alternating left to right side in order to minimize the risk of a central constraint [19]. Execution of all exercise was standardized to optimize activation of targeted muscles, and included execution in the most clinically effective portion of elastic resistance [2,9,[20][21][22].…”
Section: Interventionsmentioning
confidence: 99%
“…free radicals; peripheral fatigue; ascorbate SKELETAL MUSCLE DYSFUNCTION plays a prominent role in limiting exercise and activities of daily living in patients with chronic obstructive pulmonary disease (COPD) (21,22). Numerous factors, including inactivity and skeletal muscle detraining (34), mitochondrial dysfunction (9), and oxidative stress (30) have all been implicated in the skeletal muscle dysfunction associated with COPD. Of these factors, the contribution of oxidative stress to reduced exercise capacity in patients with COPD has been well documented (11,13,24).…”
mentioning
confidence: 99%